2020
DOI: 10.34087/cbusbed.656592
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Determining the Level of Trust in Physicians

Abstract: Güven kavramı, hasta-hekim ilişkisinin temelini oluşturmaktadır. Bu araştırma ile toplumun hekimlere güven düzeyinin belirlenmesi ve hekimlere güven düzeyinin demografik değişkenlere göre istatistiksel olarak farklılaşıp farklılaşmadığının ortaya konulması amaçlanmıştır. Gereç ve Yöntemler: Tanımlayıcı ve kesitsel tipte planlanan araştırma, Ekim 2019'da İstanbul'da gerçekleştirilmiştir. Araştırma evrenini İstanbul'da ikamet eden ve 18 yaşını doldurmuş bireyler oluşturmuştur. Araştırmada veri toplamak için anke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
1
1
0
4
Order By: Relevance
“…A meaningful difference was not found between gender, marital status, income level, frequency of hospital visits, previous hospitalization status, ability to ask questions to the doctor about oneself, doctor's ability to keep patient secrets, and sub-dimension and total STCIPPR scores. In different studies, marital status was not a factor that affected the level of trust in the physician (Gezergün et al, 2006;Gülcemal&Keklik, 2016;Deniz & Çimen, 2021). These results are similar to the ndings of our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A meaningful difference was not found between gender, marital status, income level, frequency of hospital visits, previous hospitalization status, ability to ask questions to the doctor about oneself, doctor's ability to keep patient secrets, and sub-dimension and total STCIPPR scores. In different studies, marital status was not a factor that affected the level of trust in the physician (Gezergün et al, 2006;Gülcemal&Keklik, 2016;Deniz & Çimen, 2021). These results are similar to the ndings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, studies conducted with patients have found that people with higher education levels have less trust in physicians (Yılmaz &Baysal Akkaya, 2009;Gülcemal&Keklik, 2016). In a study by Deniz & Çimen (2021), participants who had bachelor's and postgraduate degrees had lower levels of trust in the physicians. In another study, the education level was not a factor affecting the trust in the physician (Gezergün et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Deniz ve Çimen'in yaptığı araştırma sonuçları temel alınarak yapılan analizde, sağlık arama davranışı puan ortalamaları kullanılmış olup, %80 güç, %95 güven aralığı ve 0,45 etki düzeyinde çalışmaya 220 birey alınmıştır. 19 On sekiz yaş ve üzeri olan, en az bir kronik hastalık tanısı olan, Türkçe konuşan, bilişsel sorunu olmayan ve araştırmaya katılmaya onam veren bireyler çalışmaya dâhil edilmiştir. Yoğun bakımda yatan, iletişim kurmayı engelleyici akut bir sorunu olan, kronik hastalık tanısını yeni alan bireyler ve nöropsikiyatrik hastalık tanısı olan bireyler çalışmaya dâhil edilmemiştir.…”
Section: Araştirmanin Evreni̇ Ve öRneklemi̇unclassified
“…Literatür incelendiğinde, ülkemizde kronik hastalığı olan bireylerde öz yönetim ve sağlık arama davranışlarını birlikte inceleyen bir çalışmaya rastlanılmamıştır. 3,15,19…”
unclassified
“…Doktor ve hemşirelerin kaygı düzeyini arttıran durumlar hatalı tıbbi uygulama (malpraktis), yetersiz eğitim, gelecek, maddi olanaksızlıklar, olumsuz koşullar olarak belirlenmiştir. 14 Hipotez 6. Fiziksel, zihinsel ve duygusal iş yorgunluğu ile işten ayrılma niyeti arasında pozitif yönlü ilişki vardır.…”
Section: Introductionunclassified